Teachers’ perceptions on introducing sensitive and controversial issues in the classroom - Karousiou, Christiana; Vrikki, Maria; Evagorou, Maria (Frontiers in Education, 2025)
Teaching sensitive and controversial issues (SCIs) has gained substantial attention in today’s highly diverse societies. Even though it is regarded as a fundamental aspect of democratic education, many teachers refrain from undertaking this ambitious task as they feel inadequate to meet its challenges. This paper draws on focus group data on teachers’ perceptions toward introducing SCIs in their classrooms. The purposively selected sample consisted of 11 teachers from three different educational levels in the Republic of Cyprus. The data revealed contextual and professional factors that affect teachers’ decision to introduce the discussion of SCIs in the classroom. This research highlights the importance of including SCIs in the curriculum, providing efficient training and support, and equipping teachers with the necessary pedagogical strategies, knowledge, and skills to effectively navigate discussions around SCIs in the classroom. By promoting critical thinking, empathy, and respect through the inclusion of SCIs and supporting teachers in their implementation, schools can empower students to become informed and active participants in a democratic society.